Interrelated values between Bhineka Tunggal Ika and religious moderation to strengthen pluralism in Indonesia - Apandie, Chris; Rahmelia, Silvia; Risvan, Latupeirissa; Kodun, Nadi (Universitas Negeri Yogyakarta, 2022)
Along this times, motto or watchword is no longer interpreted as values that must be transmitted. This condition also causes polarization in society. The purpose of this research is to identify and elaborate the values contained in Bhinneka Tunggal Ika and Religious Moderation to strengthen conception and practices of pluralism in Indonesia. This research used qualitative approach with a case study method. Data collection were performed by Focus Group Discussion (FGD) with experts in fields of multicultural education, historian and philologist. Based on results, interrelated values between Bhinneka Tunggal Ika and religious moderation are togetherness, justice, respect and harmony. Researchers also found several interpretations by this research on findings and discussion, i.e 1) Religious moderation teaches how to respond the differences, this is accordance with the principle of unity within diversity in Bhinneka Tunggal Ika; 2) Justice can realized not only when we act in an equality, but also when we are able to live coexistence where there is no envy of each other; 3) Conception of respect and empathy is a national commitment and part of togetherness value in Bhinneka Tunggal Ika; 4) Public empathy as an encouragement from collective awareness and also a sense of togetherness is several background for embodiment of behavior in implementation Bhinneka Tunggal Ika and religious moderation. From these values, step to put forward are mainstreaming of justice principle and recognition of different entities to strengthen pluralism in Indonesia both in education and wider community.